Comparison of heavy metal concentrations in sediments, litter and plants from three different mangrove habitats in Selangor / Zhang Xue Mei - Zhang, Xue Mei (2017)
In recent years, mangroves have become a massive pollution sink which receives a number of pollutants from various sources. An experiment was conducted to determine the heavy metal concentrations in sediments, litter and plants at different mangrove habitats at the Klang Islands. Three different land use types of mangrove ecosystems were selected: natural mangrove forest (Pulau Kelang) and two types of disturbed mangrove habitats due to agriculture (Pulau Carey) and industry (Telok Gong). This study focuses on correlating the concentrations of heavy metals in sediment between tidal gradients and identifying pollution level using the geoaccumulation index. The heavy metal concentrations were also compared between different land use types. Other aims of this study were to investigate the ability of plants to absorb heavy metals in sediments in terms of an accumulation coefficient, compare the accumulation and cycle of heavy metals in mangrove sediments, fresh tissues, and litter tissues, as well as correlate the concentrations of heavy metals between sediments and different tissues of mangrove plants. The results showed that the concentrations of Pb, Hg, Cd and As of the sediments were in the order of Pb > As > Cd > Hg. At the same time, the concentrations of these heavy metals in the sediments showed some correlation with the tidal gradient but this was not significant. According to the geoaccumulation Index (Igeo), the four heavy metals in all samplings were uncontaminated to moderately contaminated (Class 1). In addition, the concentrations of heavy metals were different between land use types, whereby Telok Gong mangrove had significantly higher heavy metal concentrations than Pulau Carey mangrove. In terms of heavy metals in sediments, the accumulation coefficient values for the plant branch were Hg> Pb> Cd> As, while those for the leaves were Hg > Pb > As > Cd. The concentrations of Pb, Hg, Cd and As in mangroves were as follows: sediments > litter (branch and leaves) > fresh specimens (branch and leaves). Finally, this study showed that the concentrations of Pb, Hg and Cd were higher in branch as compared to leaves, while that of As was similar between branch and leaves.